2017
DOI: 10.1371/journal.pone.0181504
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and systematics of native North American lumbricid earthworms (Clitellata: Megadrili)

Abstract: The family Lumbricidae is arguably the most well-known and well-studied earthworm group due to its dominance in the European earthworm fauna and its invasion in temperate regions worldwide. However, its North American members, especially the genus Bimastos Moore, 1893, are poorly understood. We revised the systematics of the genus Bimastos and tested the hypothesis of the monophyly of North American lumbricids using morphological characters and eight molecular markers. Phylogenetic analyses based on our extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
1
36
0
1
Order By: Relevance
“…Dendrobaena skipetarica Szederjesi & Csuzdi, 2017in: Szederjesi et al 2017b. Dendrobaena ganglbaeri (part.…”
Section: Dendrobaena Skipetarica Szederjesi and Csuzdi 2017unclassified
“…Dendrobaena skipetarica Szederjesi & Csuzdi, 2017in: Szederjesi et al 2017b. Dendrobaena ganglbaeri (part.…”
Section: Dendrobaena Skipetarica Szederjesi and Csuzdi 2017unclassified
“…In recent research, mitochondrial COI, COII, NDI, 12S rRNA and 16S rRNA have been widely used to study the phylogenetic evaluation, mitochondrial diversity and population genetic diversity of earthworm using multivariate concatenation [18,21,[23][24][25][26][27][28][29]. Complete mitochondrial genomes and genomic features of four pheretimoid earthworms (Amynthas longisiphonus, Amynthas corticis, Amynthas gracilis and Metaphire californica) revealed that mitochondrial ATP8 exhibited the highest evolutionary rate and the NADH gene was second to it [30].…”
Section: Introductionmentioning
confidence: 99%
“…Two specimen identifications were made using molecular data: those of Aporrectodea caliginosa and Bimastos rubidus (known as Dendrodrilus rubidus prior to Csuzdi et al (2017)), which correspond with the following DNA barcode records on BOLD (Ratnasingham and Hebert 2007): (MOBIL6686-18) and (MOBIL6651-18) respectively. The latter species was also identified using the key in Reynolds (1977).…”
Section: Resultsmentioning
confidence: 99%
“…Four of these species were documented from opportunistic collections, with the standardised sampling adding one species, Dendrobaena octaedra . At least four of these species are European, or potentially Asian, introductions to North America (Reynolds 2015, Csuzdi et al 2017). One species, Bimastos rubidus , known from the most sites (n=5), is thought to be native to North America (Schwert 1979, Csuzdi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation